Causal Relationships between Academic Procrastination, Emotion Regulation and Academic Well-Being in Student: A Gender Diffrence Test - Atiyeh Motevassel; Jalil Fathabadi; Omid Shokri (پژوهشنامه روانشناسی مثبت)
This study aims to test the mediating role of emotion regulation in relation to academic procrastination with the academic well-being of male and female students. In the present study, 379 students (221 boys and 158 girls) completed the scale of Academic Procrastination, School Engagement Inventory, School Burnout Inventory, and Emotion Cognition Regulation Questionnaire. To test the mediation role of emotion regulation in the relationship between academic procrastination with academic well-being, the statistical method of structural equation modeling (SEM) was used. The results showed that emotion regulation mediated the relationship between academic procrastination and academic well-being. In addition, the results of group allocation of relationships between multiple variables showed the relationships between emotion regulation, academic procrastination and academic well-being were equal in both groups of adolescent girls and boys. Also, the results indicated that all regression weights were statistically significant. In the proposed model, an outstanding percentage of the variance of school engagement and school burnout scores were explained through academic procrastination and positive and negative cognitive emotion regulation strategies. The results highlight the role of emotion regulation such as cognitive emotion regulation strategies of male and female learners in predicting their academic performance in the face of challenging situations.IntroductionEducational researchers studying academic well-being often focus on academic burnout and engagement. Burnout, characterized by emotional exhaustion, feelings of inadequacy, and cynicism, reflects psychological well-being in academic settings (Asikainen et al., 2020; Salmela-Aro et al., 2009). Studies indicate that academic procrastination negatively impacts adolescents' well-being. Procrastination is considered a negative emotion regulation strategy, as it temporarily alleviates negative emotions and provides short-term relief. Emotion regulation strategies involve actions that influence emotions or their expression. These strategies play a key role in preventing burnout and fostering engagement. Students with high academic well-being experience positive emotions, while those with low well-being often face negative emotions like anxiety and depression (Tuominen et al.). Winga et al. found that fatigue was the most common aspect of burnout in schools, while Lam et al. reported that girls showed higher academic engagement and were rated by teachers as performing better than boys.  MethodThe study population included all male and female high school students from districts 1 to 15 of Tehran during the 2019-2020 academic year. A total of 379 10th–12th-grade students from humanities, experimental sciences, mathematics, and graphics fields were selected via convenience sampling. Data were collected using the Cognitive Emotion Regulation Questionnaire, Academic Engagement Inventory, Academic Burnout Inventory, and Procrastination Scale. Due to COVID-19, the questionnaires were distributed online through a shared link on social media. Structural equation modeling (SEM) was conducted using SPSS (v25) and Amos software.  ResultsTable1Correlation of Procrastination, Emotion Regulation, Engagement, and Burnout in Male and Female Students Commitment and InfatuationEnergyFatigue and suspicionInadequacyProcrastination girlboygirlboygirlboygirlboygirlboyAcademic -Procrastination-0.31**-0.36**-0.29**-0.38**0.64**0.58**0.27**0.21**  Self-Blame-0.17**-0.25**0.15*-0.22**0.19**0.21**0.24**0.20**0.16*0.18**Rumination-0.28**-0.24**-0.21**-0.24**0.14*0.18**0.34**0.15*0.18**0.21**Catastrophic-0.43**-0.24**0.32**-0.14**0.29*0.24**0.29**0.27**0.31**0.26**Other-Blame-0.29**-0.24**-0.48**-0.15**0.45**0.31**0.14**0.21**0.38**0.29**Acceptance0.18**0.24**0.21**0.24**-0.14**-0.18**-0.21**-0.15**-0.19**-0.20**Refocusing on Planning0.17*0.26**0.30**0.30**-0.18**-0.23**-0.19**-0.14**-0.41**-0.23**Replanning0.33**0.26**0.35**0.30**-0.45**-0.23**-0.14**-0.20**-0.34**-0.34**Positive Reappraisal0.38**0.22**0.32**0.25**-0.42**-0.23**-0.18**-0.18**-0.18**-0.35**Downplaying0.19**-0.20**0.21**0.14*-0.19**-0.20**-0.15**-0.18**-0.16**-0.20**p* < 0.05, p** < 0.01Table 1 shows that for both boys and girls, academic procrastination was negatively and significantly related to academic engagement (commitment, fascination, energy) and positively related to academic burnout (fatigue, cynicism, inadequacy) at p=0.01. Positive cognitive emotion regulation strategies (e.g., acceptance, downplaying, positive refocusing, planning) were positively related to academic engagement and negatively to burnout, both at p=0.01. Conversely, negative strategies (e.g., self-blame, other-blame, catastrophizing, rumination) were positively associated with burnout and negatively with engagement, also at p=0.01.    Figure 1Mediation Model of Cognitive Emotion Regulation in Procrastination and Academic Well-being in Adolescents  Figure 1 shows the complete mediating structural model of positive and negative cognitive emotion regulation strategies in the relationship between academic procrastination and academic engagement and academic burnout (academic well-being) in a sample of female, male and total adolescents before and after correction.The structural model revealed significant path coefficients. Academic procrastination was negatively linked to engagement and positively to burnout in both genders. Positive emotion regulation strategies were associated with higher engagement and lower burnout, while negative strategies showed the reverse. Procrastination correlated negatively with adaptive strategies and positively with non-adaptive ones.  Table2Gender Invariance of the Hypothesized Partial Mediation Model of Emotion RegulationModelLimitation/No Limitx2/df2xCFIGFIAGFIRMSEAdx2ΔdfPNo LimitsLimitless model 217.661.780.9390.9240.9020.064---RestrictedModel of Measurement Weights236.651.800.9330.9190.90.06418.591419.0Structural Weights Model240.391.730.9360.9160.90.04422.731716.0Covariance Structure Model244.571.750.9340.9150.90.04526.921810.0The immutability of the measurement model was tested in two groups of male and female adolescents. In a multi-group structural equation model, the two groups were constrained by the requirement that all independent factor loadings be equal across the groups. The results showed that the model fit the data very well (Table 2).ConclusionThe present study aimed to examine the gender equivalence of a model exploring the mediating role of cognitive emotion regulation strategies in the relationship between academic procrastination and academic well-being (burnout and engagement). The findings showed that academic procrastination was positively associated with academic burnout and negatively associated with academic engagement in both genders. Additionally, the results showed the hypothesis that academic procrastination positively correlated with negative emotion regulation strategies and negatively with positive ones. This aligns with prior research by (Mehrabi Far et al.  (2022) and Zarei and Khoshouei (2022), which found a link between higher academic procrastination and greater difficulty in emotion regulation.The study also revealed that positive cognitive emotion regulation strategies were positively associated with academic engagement and negatively with academic burnout. Conversely, negative cognitive emotion regulation strategies were negatively linked to academic engagement and positively to academic burnout. These results are consistent with Tuominen et al.’s results on the influence of academic well-being on emotional experiences and with findings by (Sirois & Pychyl, 2013) regarding the mediating role of cognitive emotion regulation in academic outcomes. Of course the results of this study are limited to the study’s cross-sectional design and the potential for inaccurate responses due to online self-report questionnaires. Future studies should consider larger populations and longitudinal designs, incorporating behavioral observations in natural settings to enhance generalizability. Additionally, teaching cognitive emotion regulation strategies is recommended for reducing academic procrastination and improving students' academic well-being. Ethical ConsiderationThis study was approved by the relevant ethical review board, and informed consent was obtained from all participants. Participants were fully informed about the study's purpose, procedures, and their rights, including the option to withdraw at any time. Confidentiality and anonymity were maintained by safeguarding all personal data. The research adhered to [specific ethical guidelines] and complied with institutional and legal requirements to ensure minimal risk and protect participant welfare.Compliance with Ethical GuidelinesThis work complies with all relevant ethical standards. For research involving human participants or animals, ethical approval was obtained, and informed consent was secured. The authors declare no conflicts of interest, adhere to data integrity and transparency, and acknowledge all sources and contributions appropriately.Authors’ ContributionsJalil Fathabadi and Omid Shokri supervised the project. Atiyeh Motevassel conducted the experiments, collected data, performed the initial analysis, and prepared the manuscript draft. All authors reviewed and approved the final manuscript.Conflict of InterestThe author(s) declare no conflicts of interest regarding the research, authorship, or publication of this paper. All relevant disclosures have been made and managed appropriately.FundingThis research received no specific grant from any funding agency in the public, commercial, or not-for-profit sectors.